Effectiveness of Selected Entomopathogenic Fungi in Packed Rice Grain at Room Temperature Against Corcyra Cephalonica Stainton - Hendrawan Samodra; Yusof Bin Ibrahim (ASEAN Journal on Science and Technology for Development, 2006)
Eight isolates of entomopathogenic fungi were evaluated as dried conidia against the rice moth,  Corcyra cephalonica. In bioassays two isolates of Beauveria bassiana (BbGc and BbPs) and one isolate of Metarhizium anisopliae (MaPs) consistently gave high mortality to C. cephalonica larvae. Formulations in either kaolin, talc or tapioca flour (20 % w/w a.i.) thoroughly mixed with long grain rice in plastic cups (8 cm diameter by 5 cm) gave complete larval mortality by the 12th day of treatment. However, in general those formulated in kaolin and talc were more efficacious and faster to kill compared to those formulated in tapioca flour or the unformulated control. Even at the lowest rate of 0.05 g BbGc in kaolin provided 100% mortality 7 days after introduction compared with other dust formulations. Isolate BbGc in kaolin and talc administered at 0.4 g a.i. in 200 g rice packed in plastic kept at room temperature provided protection against the rice moth up to 4 months of storage. Larval mortality in excess of 90% was obtained 15 days after introduction. Formulations of MaPs was effective only within the first month of storage beyond which infectivity rapidly declined.